Perception of Prevention Stunting Through Healthy Lifestyle in Adolescent Girls: Case Study of Adolescents in Bantul, Yogyakarta - Dina Fitriana Rosyada; Marko Ferdian Salim; M. Syairaji (Poltekkes Kemenkes Jakarta III, 2020)
stunting is one of the targets of sustainable development goals (SDGs) included in the second sustainable development goal of eliminating hunger and all forms of malnutrition by 2030 and achieving food security. Indonesia is included in the third country with the highest stunting prevalence in the south-east Asia region (sear). One of the regions in java where there are stunting cases is in Yogyakarta, namely in Bantul Regency. This research aims to determine the perception of young women about stunting prevention through healthy living. This research is qualitative research with a case study approach. The variable in this study is the perception of young women regarding the prevention of stunting through a healthy lifestyle. This research concluded that some female subjects already understood the definition of stunting but did not yet know the important role of adolescents in the prevention of stunting before pregnancy. This shows that there is no appropriate perception among adolescents regarding the prevention of stunting with a healthy lifestyle since early adolescence. If the adolescent is not repaired, so in the future, there will be more and more expectant mothers who have short body posture and/or lack of chronic energy.